Etching strategy synthesis of hierarchical Ni-Mn hydroxide hollow spheres for supercapacitors. (January 2021) - Cheng, Cheng; Wei, Chengzhen; He, Yuyan; Liu, Lingyun; Hu, Jingyue; Du, Weimin
Highlights: An effective etching strategy has developed for the synthesis of hierarchical Ni-Mn hydroxide hollow spheres. As an advanced electrode material, a large specific capacity of 1680 F g −1 at 2.0 A g −1 can be achieved. The assembled Ni-Mn hydroxide//AC ASC device exhibited high specific power and energy. Abstract: Hierarchical hollow structures have been shown excellent performance in supercapacitors. Herein, hierarchical Ni-Mn hydroxide hollow spheres are successfully prepared by an etching strategy. NiMn-glycerate solid spheres are first obtained as templates. After treatment in the mixed solvents of 1-methyl-2-pyrrolidone and water, NiMn-glycerate templates are etched to form hierarchical Ni-Mn hydroxide hollow spheres. Owing to the advantages of hierarchical hollow structures and large surface area, Ni-Mn hydroxide as electrode material manifests a specific capacity of 1680 F g −1 at 2.0 A g −1, and it maintains 1068 F g −1 at 15 A g −1 . Meanwhile, a diminished specific capacity of only 3.4 % is achieved over 5500 cycles at 10 A g −1 . Furthermore, the fabricated asymmetric supercapacitor comprising of Ni-Mn hydroxide and activated carbon demonstrates a specific energy of 42.8 Wh kg −1 at 1703 W kg −1, indicating as a promising electrode material for high performance supercapacitors. Graphical abstract: Image, graphical abstract